Analysis Of Problems Faced By Special Education Teacher In Teaching The Multiple Disabilities Students - Azhar Alias; Norshidah Mohamad Salleh (Journal of ICSAR, 2017)
Multiple disabilities were defined as a person with two or more disabilities. It had caused a lot of problems in teaching and learning because they need specific education. The main objective of this study is to identify and determine the priority level of the problems faced by special education teachers in teaching multiple disabilities students. This study was based on Maslow’s Motivational Theory that focusing on Maslow’s Hierarchy of Needs. This survey had implemented questionnaire instrument that had been adapted from Oklahoma Office of Handicapped Concerns: 2001-2002 Disability Assessment Study. Interview protocol was adapted from National Center For Postsecondary Improvement and was implemented to identify other problems. The respondents were 66 special education teachers from 18 schools in Muar distric and 18 others were for interview session that were choosen using purposive sampling. The datas were analyzed using the IBM SPSS Statistic Version 22 by comparing mean and the findings from the interview were analyzed narratively. Both findings were devided into 3 levels which were low, medium and high according to mean value and percentage of respondent agreements. This study had found 12 problems (mean=3.97, s.d=0.916) and the 4 main problems according to priority were (1) lack of specific teaching aids (mean=4.15, s.d=0.808) (2) low self motivation and self confident (mean=4.14, s.d=0.857) (3) lack of aids support (mean=4.12, s.d=0.851) (4) communication problems (mean=4.09, s.d=0.872). The findings from the interview had came up with 15 problems and the 5 main problems according to priority were (1) emotional disturbance and lack of concentration (2) non-condusive environment in the classroom (3) communication problems (4) low cognitive level (5) lack of specific teaching aids. These findings were seen as good indicators for the authorities and special education teachers to develop and improve the education system, teaching pedagogy and high quality level of profesionalism among special education teachers.